A voz dos olhares que percorrem a periferia: o território sob as lentes do adolescente - Dantas, Joao Gabriel Trajano [UNIFESP] (2019)
The outskirts of São Paulo is marked by situations of social inequality, violence and poverty. It is a fertile territory full of vulnerabilities and potentialities, aspects that only their residents can identify them. Adolescence is marked by the search for new experiences of pleasure and feelings of belonging to a social group are actors ideal for photographing the potentialities and weaknesses of the territory in which they live and structure your daily life. Thus, this exploratory qualitative study, which used the photography as a methodological resource, sought to investigate the perception that adolescents residents in a slum have over the territory in which they live. So cameras were distributed to the participants, who in turn photographed dimensions related to leisure, socializing, sports and entertainment found in space, as well as recorded aspects that need more government attention, such as garbage and rubble placed on sidewalks, polluted springs and finally, valued the organization maintenance and revitalization of squares and the soccer field, showing that the Their youth are attentive to the complex issues of the territory in which they live.